Effect of stroke on arginase expression and localization in the rat brain. Issue 7 (13th January 2013) - Quirié, Aurore; Demougeot, Céline; Bertrand, Nathalie; Mossiat, Claude; Garnier, Philippe; Marie, Christine; Prigent‐Tessier, Anne
Abstract Because arginase and nitric oxide (NO) synthases (NOS) compete to degrade l‐arginine, arginase plays a crucial role in the modulation of NO production. Moreover, the arginase 1 isoform is a marker of M2 phenotype macrophages that play a key role in tissue remodeling and resolution of inflammation. While NO has been extensively investigated in ischemic stroke, the effect of stroke on the arginase pathway is unknown. The present study focuses on arginase expression/activity and localization before and after (1, 8, 15 and 30 days) the photothrombotic ischemic stroke model. This model results in a cortical lesion that reaches maximal volume at day 1 post‐stroke and then decreases as a result of astrocytic scar formation. Before stroke, arginase 1 and 2 expressions were restricted to neurons. Stroke resulted in up‐regulation of arginase 1 and increased arginase activity in the region centered on the lesion where inflammatory cells are present. These changes were associated with an early and long‐lasting arginase 1 up‐regulation in activated macrophages and astrocytes and a delayed arginase 1 down‐regulation in neurons at the vicinity of the lesion. A linear positive correlation was observed between expressions of arginase 1 and glial fibrillary acidic protein as a marker of activated astrocytes. Moreover, the pattern of arginase 1 and brain‐derived neurotrophic factor (BDNF) expressions in activated astrocytes was similar. Unlike arginase 1, arginase 2 expression was not changed by stroke. In conclusion, increased arginase 1 expression is not restricted to macrophages in inflammation elicited by stroke but also occurs in activated astrocytes where it may contribute to neuroplasticity through the control of BDNF production.